Fractal video compression using discrete cosine transformation - Brozo, Ryan C. (2000)
The hybrid image compression scheme proposed in this paper is a block-based fractal coding and discrete cosine transform (DCT). Each pixel in the image is split into its three color components, namely R(Red(, G(Green) and B(Blue). From there, the luminance (Y) and chrominance (I and Q) components are computed. The luminance component (Y) is then compressed by the DCT domain fractal transform instead of spatial domain fractal transform. Afterwards, the chrominance component (I and Q) is also compressed using fractals. This scheme is later on extended to video files. The progression is logical, since a video file is simply a collection of still frames of images. The detailed steps to implement the scheme are presented later.